ESTIMATING ENERGY SAVING POTENTIAL BY TAKING INTO ACCOUNT INTERDEPENDENCE EFFECT CASE STUDY: HIGH RISE OFFICE BUILDING IN JAKARTA - Endang Widayati (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2021)
Abstract: The purpose of this study is making comparison between calculation of the potential for energy savings without and with taking into account the interdependency effect based on a case study in a conditioned high rise office building in Jakarta. Accurate estimation of the energy saving potential will increase the confidence level in bankable investment of energy saving projects. This will minimize the uncertainty of achievable energy savings which can prevent investment risks during implementing energy conservation and efficiency projects. The results of this study based on a study case, indicate that estimated energy savings of ESM-1 e.g. retrofit of lighting increase 4.29% when the interdependency effect is taking into account. ESM-2 e.g. installation of variable speed drive (VSD) on the air handling unit (AHU) shows the estimated energy saving increase 22.75% by taking into account interdependency effect. The effect of this interdependence both ESM-1 and ESM-2 is a reduction in cooling load in buildings. Totally, the calculation of the interdependency effect will increase the percentage of the total estimate of potential energy savings from 34.23% to 39.05% based on the energy baseline with a predefined baseyear periode, around 4.82% increased. The calculation of the interdependency effect will be very influential in minimizing uncertainty when the projects are financed by an energy performance contract mechanism whether a guaranteed or shared saving scheme. The measurement and verification energy saving during reporting period should be conducted in the future to compare the energy saving projection before ESMs implementation and measurement and verification results.